2014
DOI: 10.1097/qai.0000000000000167
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy in Primary HIV Infection Associates With Systemic and Central Nervous System Immune Activation

Abstract: Background Peripheral neuropathy (PN) is a frequent complication of chronic HIV infection. We prospectively studied individuals with primary HIV infection (PHI, <1 year after transmission) to assess the presence of and laboratory associations with PN in this early stage. Methods Standardized examination and analysis of blood and cerebrospinal fluid (CSF) was performed in participants with laboratory-confirmed PHI. PN was defined as ≥1 of the following unilateral or bilateral signs: decreased distal limb posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Distal sensory polyneuropathy has been found to occur at the early stage of primary HIV infection due to high rate of activated macrophage, cytokines, and chemokines infiltration in the CNS resulting from systemic and nervous system immune responses [25]. Studies in the SIV-infected primate models have shown that primary HIV-infection induces sensory neuropathy by damaging dorsal root ganglia nerve fibers and intra-epidermal nerve fiber density [26, 27].…”
Section: Neuro-muscular Complications In Hiv-associated Sensory Neuromentioning
confidence: 99%
“…Distal sensory polyneuropathy has been found to occur at the early stage of primary HIV infection due to high rate of activated macrophage, cytokines, and chemokines infiltration in the CNS resulting from systemic and nervous system immune responses [25]. Studies in the SIV-infected primate models have shown that primary HIV-infection induces sensory neuropathy by damaging dorsal root ganglia nerve fibers and intra-epidermal nerve fiber density [26, 27].…”
Section: Neuro-muscular Complications In Hiv-associated Sensory Neuromentioning
confidence: 99%
“…Such microbial translocation most likely leads to local and systemic immune activation, characterized by increased levels of pro-inflammatory cytokines such as tumour-necrosis-factor α (TNF-α), neopterin, cluster of differentiation 14 (CD14), interleukin-8 (IL-8), and interleukin-6 (IL-6) [6], [7], [8], [9]. In particular, plasma neopterin is an established marker of monocyte activation and was repeatedly associated with HIV disease progression, greater peripheral monocyte HIV DNA reservoirs and negative neurocognitive and cardiovascular outcomes [10], [11], [12]. …”
Section: Introductionmentioning
confidence: 99%
“…HIV infiltrates the CNS during PHI [6][7][8], as indicated by the presence of HIV RNA in the cerebrospinal fluid (CSF) compartment, even in the absence of neurological symptoms [1,[8][9][10][11]. CNS immune activation accompanies this viral invasion, as reflected by elevations in the CSF white blood cell count and the soluble CSF biomarkers neopterin (reflecting macrophage activation) and CXCL-10/IP-10 (a lymphocyte chemokine) and by T-lymphocyte activation in CSF [1,[12][13][14][15]. Furthermore, markers of immune activation may reflect the degree of viral load and neurocognitive impairment [16].…”
mentioning
confidence: 99%